2022
DOI: 10.48550/arxiv.2207.10099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spin-Resolved Topology and Partial Axion Angles in Three-Dimensional Insulators

Abstract: Topological insulating (TI) phases were originally highlighted for their disorder-robust bulk responses, such as the quantized Hall conductivity of 2D Chern insulators. With the discovery of time-reversal-(T -) invariant 2D TIs, and the recognition that their spin Hall conductivity is generically non-quantized, focus has since shifted to boundary states as signatures of 2D and 3D TIs and symmetry-enforced topological crystalline insulators (TCIs). However, in T -invariant (helical) 3D TCIs such as bismuth, BiB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…IV. Our work can also be extended to (interacting and noninteracting) time-reversal invariant HOTI phases in 2D, where we expect to find spinresolved responses [112][113][114] and charge-neutral defect states [56,69]. Such an extension would be particularly relevant to experimental searches for non-magnetic obstructed atomic limit phases [115][116][117].…”
Section: Discussion and Future Directionsmentioning
confidence: 93%
“…IV. Our work can also be extended to (interacting and noninteracting) time-reversal invariant HOTI phases in 2D, where we expect to find spinresolved responses [112][113][114] and charge-neutral defect states [56,69]. Such an extension would be particularly relevant to experimental searches for non-magnetic obstructed atomic limit phases [115][116][117].…”
Section: Discussion and Future Directionsmentioning
confidence: 93%
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. supported built-in functionality for computing state-of-the-art topological diagnostics including the nested Wilson loop [13,14] and the spin-resolved Wilson loop [15,16]. Both computations are critical for a comprehensive analysis of band topology.…”
Section: Introductionmentioning
confidence: 99%
“…Both computations are critical for a comprehensive analysis of band topology. Recently, an auxiliary code was constructed to work in conjunction with the PythTB package for the computation of these quantities [16]. However, as mentioned, each code has separate strengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key role of inversion symmetry has been further explored in highdimensional systems in the context of fragile topology both in free [21][22][23][24][25][26][27][28][29] and in interacting systems [30][31][32][33][34][35]. Moreover, it has been shown that the combination of inversion and time reversal symmetries plays a central role in various kinds of higher-order topological insulators (HOTIs) in high dimensionality [27,[36][37][38][39][40][41][42][43][44][45]. Topological states of matter result to be much less understood in presence of interactions.…”
mentioning
confidence: 99%